Evaluation of Chemical and Physical Properties of Commercial Sandalwood Essential Oils and their Comparison with Essential Oil Extracted from Santalum album L. Issue 2 (3rd March 2020) - Bisht, Surendra Singh; Chandra, Girish; Ravindra, Mamata; Kumar, Rakesh
Abstract: Indian sandalwood oil is an essential oil (EO) obtained from the heartwood of Santalum album L tree. Thirty-eight sandalwood (SW) EO samples, including ten samples from heartwood of S. album and twenty-eight trade samples of SW EOs, were assessed for refractive index (RI), relative density (RD) and α- and β-santalol content. RI and RD values were found within the ranges of 1.4554 to 1.5035 and 0.943 to 1.472 respectively. The percentage of α- and β-santalols in these samples ranged from 0 to 54.28 % and 0 to 25.94 % respectively. The EO samples with α- and β-santalol content from 48.2 to 54.28 % and 19.15 to 25.94 % respectively were comparable with the pure sandalwood EO as described in Indian Standard (IS329-2004). Only about less than one third of the commercial SW EOs met with IS329-2004. The statistical significant difference and prioritization analysis were checked by Duncan's Multiple Range Test and Grey Relational Analysis method, respectively. The presence of the adulterants diethyl phthalate (DEP) and diethylhexyl phthalate (DEHP) in some of the EOs were ascertained and quantified by respective standard and regression curve of standard. Very high content of DEP (up to 4.4 x10 5 ppm) and DEHP (up to 8.0 x10 5 ppm) were detected in some of the commercially available sandalwood EOs. Thus, it is concluded that quality control and authentication for high valued sandalwood EO should mainly rely on its physical (RI and RD), chemical analysis (level of α- and β-santalol content).